Circadian Rhythm and Melatonin in the Treatment of Depression - Satyanarayanan, Senthil K.; Su, Huanxing; Lin, Yi-Wen; Su, Kuan-Pin (Current Pharmaceutical Design, 2018)
Background: Circadian rhythm disruption underlies the pathophysiology of psychiatric disorders, especially depression. Both pharmacological and non-pharmacological strategies affecting endogenous circadian rhythms have been developed with specificity to alter the circadian dysfunction. The current management strategy with antidepressants is far from being satisfactory in addressing this issue. In recent years, attempts at discovering new antidepressants focused on a melatonergic system which is known to be altered in depression have led to a potential option for treatment of depression. Methods: We reviewed all recently published relevant articles on melatonin and its analogues to look for their implication in the treatment of circadian rhythm disruption and depression. Results: Melatonin, a pleiotropic regulator molecule and its analogues (ramelteon, agomelatine, TIK-301, Neu- P11 and tasimelteon) have been observed to resynchronize the circadian rhythm and some were said to alleviate depressive symptoms in depressed subjects. Conclusion: This review focuses on substantial advances in the melatonin-based chronobiologic intervention and its responses in the treatment of depression.
Keywords: melatonin